Republic of Madagascar : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
Developing and boosting the private sector, in the area of industry, trade, and private sector, actions for securing investment, promoting investment, developing partnerships in Madagascar produced positive results. The investment rate is 12.37 percent out of an objective of 14 percent. The achievements in the rehabilitation of rural roads have improved compared with those of 2004, but the objectives for the year have not been achieved (65 percent). In posts and telecommunication, for the postal service, the number of savings 'Tsinjolavitra' recorded a net improvement compared with those of the previous year.